1988
DOI: 10.1021/jm00117a029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel 3-substituted .beta.-carbolines as benzodiazepine receptor ligands: probing the benzodiazepine receptor pharmacophore

Abstract: The 3-substituted beta-carbolines 2-4 and 5-7 were prepared from 3-amino-beta-carboline (8) in one step via diazotization, followed by reaction with the appropriate nucleophile in order to determine their binding affinity for benzodiazepine receptors (BzR). All three of the 3-alkoxy-beta-carbolines 2 (IC50 = 124 nM), 3 (IC50 = 24 nM), and 4 (IC50 = 11 nM) have high affinities for BzR. The beta-carbolines substituted with electron-withdrawing groups including 5 (Cl; IC50 = 45 nM), 6 (NO2; IC50 = 125 nM), and 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 5 publications
(7 reference statements)
5
107
0
Order By: Relevance
“…Methyl substitution at N(9) drastically reduces ligand affinity from IC,, = 5 nM for the P-carboline-3-carboxylic acid methyl ester (PCCM) to IC,, > 50 000 nM for its 9-methyl derivative (34), thereby suggesting the importance of this hydrogen bond. Even though the hydrogen-bonding patterns are quite different in the three structures reported here, in each case the indole N(9)-H participates in a hydrogen bond (see Table 4), which provides evidence that this group forms a hydrogen bond with the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl substitution at N(9) drastically reduces ligand affinity from IC,, = 5 nM for the P-carboline-3-carboxylic acid methyl ester (PCCM) to IC,, > 50 000 nM for its 9-methyl derivative (34), thereby suggesting the importance of this hydrogen bond. Even though the hydrogen-bonding patterns are quite different in the three structures reported here, in each case the indole N(9)-H participates in a hydrogen bond (see Table 4), which provides evidence that this group forms a hydrogen bond with the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Series B contains 17 derivatives of b-carbolines with their observed affinities (Allen et al, 1988;Hollinshead et al, 1990;Sharma et al, 1992) and are reported in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…These ligands allosterically modulate the action of GABA on neuronal chloride ion flux, thus eliciting a wide variety of pharmacological actions ranging in a continuum from Bz-like action (full agonists with anxiolytic, sedative/hypnotic, and anticonvulsant activities) to Bz-opposed action (inverse agonists with proconvulsant and anxiogenic activities), via antagonists which do not exhibit any pharmacological effects per se, but can antagonize the action of both agonists and inverse agonists [1Ϫ4]. Among these compounds, the most interesting classes are β-carbolines I [5], pyrazoloquinolines II [6,7], triazolophthalazines III [8], and pyridodiindoles IV [9] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%